1996
DOI: 10.1182/blood.v88.8.3022.bloodjournal8883022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an unusual Fc gamma receptor IIIa (CD16) on natural killer cells in a patient with recurrent infections

Abstract: We found an unusual fc gamma receptor IIIa (CD16) phenotype on the natural killer (NK) cells of a 3-year-old boy, who suffered from recurrent viral respiratory tract infections since birth. He also had severe clinical problems after Bacille Calmette-Geerin (BCG) vaccination and following Epstein-Barr virus and Varicella Zoster virus infections. His peripheral blood lymphocytes contained a normal percentage and absolute number of CD3-CD7+ cells, which were positively stained with the CD16 monoclonal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 8 publications
2
44
1
1
Order By: Relevance
“…These results agree with our finding of increased CD57 1 cells in CVID patients and are consistent with the concept of a more inflammatory pattern of pathology [24]. Although circulating NK cell numbers are clearly depleted in CVID patients, this appears to have no short-term clinical relevance, since the patients are not prone to herpes viruses, as has been reported in rare patients with isolated NK cell deficiencies [25], nor to most other viral infections. Furthermore, previous studies on in vitro cytotoxicity of PBMC from CVID patients to the K562 cell line (presumed NK activity) have been normal, suggesting a compensatory mechanism for the low numbers [4].…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with our finding of increased CD57 1 cells in CVID patients and are consistent with the concept of a more inflammatory pattern of pathology [24]. Although circulating NK cell numbers are clearly depleted in CVID patients, this appears to have no short-term clinical relevance, since the patients are not prone to herpes viruses, as has been reported in rare patients with isolated NK cell deficiencies [25], nor to most other viral infections. Furthermore, previous studies on in vitro cytotoxicity of PBMC from CVID patients to the K562 cell line (presumed NK activity) have been normal, suggesting a compensatory mechanism for the low numbers [4].…”
Section: Discussionsupporting
confidence: 92%
“…Similar analyses for FcgRIIIa and IIIb polymorphisms showed no differences between the V1 and F/F158, and NA21 and NA1/NA1 genotypes, respectively (data for FcgRIIIa also shown in Fig. 1); the numbers of teeth within the different bone loss categories were in all these cases essentially similar to the values presented in (Kobayashi et al 1997, Kobayashi et al 2000, Kobayashi et al 2001, Meisel et al 2001), viral diseases (De Vries et al 1996) and the Guillain-Barré syndrome . The present study was designed to investigate whether polymorphisms in FcgR showed an altered prevalence or were associated with severity among periodontitis patients from strictly Northern European heritage (Dutch), in comparison to controls without destructive periodontitis.…”
Section: Subgroup Analysessupporting
confidence: 73%
“…NK-cell defects present with a heterogeneous clinical phenotype and are difficult to be detected by plain measurement of total NK-cell numbers. However, patients with defects in the NK-cell system exhibit characteristic NK-cell signatures with normal NK-cell numbers but inactive function due to deletions in specific receptors (e.g., in TAP-2 deficient patients), a reduced cytotoxicity (e.g., familial lymphohistiocytosis syndromes, Hermansky-Pudlak syndrome, or Papillon-Lefevre syndrome) or due to CD16 impairment (4,(58)(59)(60). It is of importance to determine NK cells by gating CD16 versus CD56 and not by using a combined CD16/56 marker or by use of CD56 alone.…”
Section: Discussionmentioning
confidence: 99%